Artificial Intelligence in Public Governance: Ethical Opportunities and Challenges in Indonesia’s Digital Transformation - Tohopi, Rustam; Aneta, Yanti; A. Hulinggi, Pebriyanto (Indonesian Association for Public Administration (IAPA), 2025)
Purpose: This study investigates the ethical opportunities and challenges of Artificial Intelligence (AI) adoption in Indonesia’s public governance, where digital transformation has become a central agenda. It explores how global AI governance frameworks can be contextualized for developing countries with fragmented institutions, regulatory gaps, and limited capacities. Design/methodology/approach: A systematic literature review (SLR) was conducted using Scopus, Web of Science, IEEE Xplore, ACM Digital Library, SpringerLink, and Google Scholar. Publications from 2020 to August 2025 were screened through PRISMA procedures, yielding 45 eligible studies. An adapted Critical Appraisal Skills Programme (CASP) tool was applied for quality assessment. Data were synthesized thematically across governance dimensions: accountability, lifecycle governance, regulation and standards, transparency and explainability, inclusivity and equity. Findings: The review identifies both opportunities and risks of AI in Indonesia’s public sector. Opportunities include bureaucratic efficiency, transparency, and citizen-centric services. However, challenges remain: algorithmic bias, data privacy risks, unequal digital access, and regulatory fragmentation. Comparative analysis shows that while developed nations employ enforceable technical standards and independent oversight, Indonesia’s governance mechanisms remain largely normative and under-implemented. Practical implications: The study proposes a governance checklist tailored to Indonesia, emphasizing multi- level accountability, lifecycle monitoring, algorithmic audits, and participatory oversight. These findings inform policy reforms for Indonesia’s National AI Strategy (Stranas KA) and support more equitable, transparent, and accountable public sector innovation. Originality/value: This article contributes by contextualizing global AI governance frameworks within a Southeast Asian developing country, bridging the knowledge gap between normative principles and enforceable practices. It highlights pathways for adaptive governance in resource-constrained settings, with implications for scholars, policymakers, and practitioners.